Структурно-механические свойства и морфология биокерамики - Степук, А. А.; Степук, Александр Владимирович; Автономова, Людмила Владимировна (НТУ "ХПИ", 2006)
The Calcium Hydroxyapatite (HAp), which physical and chemical properties are similar to bone tissue, is applied in various medicine areas as ceramics, cements and composite implants. It is exposed that thermo treatment leads to crystallites form and structure modification. It is examined the crystallites morphology, that influence to structural and mechanical HAp properties
Keywords: материалы на основе фосфатов кальция; костная ткань; кристаллы синтетического апатита; порошки гидроксилапатита; измерение прочности на сжатие